Pengembangan Workshop Otomotif Berbasis Virtual Reality sebagai Sarana Belajar Mandiri Siswa untuk Meningkatkan Kompetensi Overhaul Mesin - Emdi Ramadana Putra; Imam Wahyudi Farid; Rico Andika Putra (Jurnal Pendidikan Indonesia, 2026)
This study addresses the limitations of motorcycle engine overhaul practice facilities, which have resulted in several students becoming passive observers and insufficiently engaged in hands-on learning activities. Such conditions have contributed to low procedural competence, reduced learning motivation, and suboptimal practical performance. The study aims to analyze, develop, and evaluate the effectiveness of a Virtual Reality (VR)-based automotive workshop in enhancing students’ cognitive and psychomotor competencies comprehensively. This research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of 30 eleventh-grade students from the Motorcycle Engineering (TBSM) program, with 10 students selected purposively for the limited trial phase. Data were collected through observations, interviews, student response questionnaires, expert validation sheets, and pretest–posttest instruments as the primary measures of learning outcomes. Data analysis was conducted using descriptive quantitative and qualitative techniques, including feasibility percentage calculations, mean score analysis, and gain score measurement to determine learning improvement. The findings indicate that the implementation of the VR-based automotive workshop significantly improved students’ competencies in motorcycle engine overhaul material. The study concludes that VR effectively addresses limitations in practical facilities and enhances students’ overhaul competencies. These findings imply that VR can be systematically integrated into vocational curricula as an innovative, technology-based solution for practical learning enhancement.